Targeted multiple biomarker approach in predicting cardiovascular events in patients with diabetes. Issue 24 (25th July 2016) - Resl, M; Clodi, M; Vila, G; Luger, A; Neuhold, S; Wurm, R; Adlbrecht, C; Strunk, G; Fritzer-Szekeres, M; Prager, R; Pacher, R; Hülsmann, M
Abstract : Objective: We hypothesised that biomarkers representing different pathophysiological pathways of atherosclerosis namely growth differentiation factor 15 (GDF-15), N-terminal pro B-type natriuretic peptide (NT-proBNP) and high-sensitive troponin T (hs-TnT) could enhance cardiovascular risk prediction in patients with type 2 diabetes mellitus. Methods: This is a prospective study in 746 patients with type 2 diabetes mellitus, who were followed up for 60 months. The primary endpoint was defined as unplanned hospitalisation for cardiovascular disease or death. The prognostic performance of the biomarkers of interest (GDF-15 in comparison with NT-proBNP and hs-TnT) was evaluated in univariate as well as in stepwise Cox regression models. HRs are presented per standard unit increase. Results: The primary endpoint was registered in 171 patients (22.9%). In univariate Cox regression models, GDF-15 as well as hs-TnT provided significant prognostic information. Even after adjusting for established cardiovascular risk factors, GDF-15, hs-TnT and NT-proBNP remained strong independent predictors of the endpoint (logGDF-15: HR 1.37, p<0.01, CI 1.12 to 1.68; loghs-TnT: HR 1.43, p<0.01, CI 1.13 to 1.1.82; logNT-proBNP: HR 1.45, p<0.01, CI 1.26 to 1.66). The number of elevated markers showed a strong complementarity to predict future long-term risk. Adding hs-TnT and GDF-15 to a zero model already including NT-proBNP led to a net reclassification improvement (NRI) of 33.6% (CI 16.0% to 50.8%, NRI for patients with event: 11.1% CI −4.7% to 26.6%, for patients without event: 22.5% CI 13.6% to 30.5%). Conclusions: GDF-15 and hs-TnT are strong independent cardiovascular biomarkers augmenting the predictive value of NT-proBNP in patients with diabetes.